Transient Absorption of Chlorophylls and Carotenoids after Two-Photon Excitation of LHCII - Šebelík, Václav; Kuznetsova, Valentyna; Lokstein, Heiko; Polívka, Tomáš (The journal of physical chemistry letters, 2021)
Femtosecond transient absorption spectroscopy following two-photon excitation (2PE) is used to determine the contributions of carotenoids and chlorophylls to the 2PE signals in the main plant light-harvesting complex (LHCII). For 2PE, excitation at 1210 and 1300 nm was used, being within the known 2PE profile of LHCII. At both excitation wavelengths, the transient absorption spectra exhibit a shape characteristic of excited chlorophylls with only a minor contribution from carotenoids. We compare the 2PE data measured for LHCII with those obtained from 2PE of a lutein/chlorophyll a mixture in acetone. We estimate that although the 2PE cross section of a single carotenoid in acetone is ∼1.7 times larger than that of a Chl a, due to the 1:3.5 carotenoid/Chl ratio in LHCII, only one-third of the absorbed 2PE photons excite carotenoids in LHCII in the 1200-1300 nm range.